Sleep, mental health and wellbeing among fathers of infants up to one year postpartum: A scoping review. (September 2020) - Wynter, Karen; Francis, Lauren M.; Fletcher, Richard; McBride, Nyanda; Dowse, Eileen; Wilson, Nathan; Di Manno, Laura; Teague, Samantha; Macdonald, Jacqui A.; ,
Highlights: This is the first review of evidence on sleep among fathers of infants 0-12 months. Poor sleep is common among fathers of infants 0 to 12 months. There is no consistency in how sleep is assessed. Poor paternal sleep co-exists with depression symptoms and impaired relationships. Links among infant sleep, father sleep and father wellbeing need further analysis. Abstract: Background: Sleep disturbance among adults has consequences for their health and functioning. Among mothers of infants, there is evidence that fatigue and sleep disturbance are significantly associated with depression, anxiety and impaired relationships with partners and infants. It is not known whether consistent evidence of such associations exists for fathers. Purpose: The aim of this review was to describe what is known about fathers' sleep and its associations with mental health and wellbeing, in the first 12 months postpartum. Methods: A scoping review was conducted, searching MEDLINE complete, Scopus, PsycINFO and CINAHL complete, from 1990 to 13 May 2019. Reference lists of relevant reviews were also searched. Articles were included if they were published in English, and reported on sleep among men cohabiting with their infants from birth to 12 months. Findings: Thirty papers reporting on 27 separate studies met inclusion criteria. Sleep constructs and assessment of these varied greatly. While some measures of fathers' sleep improved, fathers' fatigue increased significantly with increasing infant age. In adjusted analyses, fathers' sleep problems were associated with poorer mental health, relationships with partners, and safety compliance at work. Key conclusions: Health professionals should consider a brief assessment of fathers' sleep when they consult families with young infants. Psycho-education regarding management of poor infant sleep could help to prevent long-term fatigue and its consequences among fathers.